Meeting the expectations of higher education teachers and assistants for training within the INOVUP project - Matej Urbančič; Nina Kristl (University of Maribor Press, 2020)
All university teachers work with students, but not all of them are aware that the teaching approach is as important and as relevant as the subject content. Within the INOVUP project, university teachers receive training in higher education didactics to raise the quality of instruction. The main premise of the project is that the teaching method is related to the acquired knowledge, understanding of the content, motivation for work and cooperation between students and teachers. The article addresses teachers' responses to and expectations of these training events and how these expectations are met. The results show that more than three-quarters of the participants seek practical, usable knowledge. The participants are mostly satisfied with the training, which they consider to be a positive contribution to the acquisition of theoretical and practical knowledge and motivation for further deepening their knowledge. Based on these findings, recommendations can be put forward to upgrade training for future